2021
DOI: 10.1212/wnl.0000000000012702
|View full text |Cite
|
Sign up to set email alerts
|

Structural MRI Signatures in Genetic Presentations of the Frontotemporal Dementia/Motor Neuron Disease Spectrum

Abstract: Objective.To assess cortical, subcortical and cerebellar grey matter (GM) atrophy using magnetic resonance imaging (MRI) in patients with disorders of the frontotemporal lobar degeneration (FTLD) spectrum with known genetic mutations.Methods.Sixty-six patients carrying FTLD-related mutations were enrolled, including 44 with pure motor neuron disease (MND) and 22 with frontotemporal dementia (FTD). Sixty-one patients with sporadic FTLD (sFTLD) matched for age, sex and disease severity with genetic FTLD (gFTLD) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
29
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 48 publications
5
29
1
Order By: Relevance
“…In addition, this region is connected to the frontal cortex to regulate motor and premotor functions [53,54]. In contrast with previous studies [43,51,52], we did not find any significant changes in cerebellar subregions in the ALS group. It may be that parcellating the cerebellum into smaller subregions reduces our capacity to detect significant differences in this group.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…In addition, this region is connected to the frontal cortex to regulate motor and premotor functions [53,54]. In contrast with previous studies [43,51,52], we did not find any significant changes in cerebellar subregions in the ALS group. It may be that parcellating the cerebellum into smaller subregions reduces our capacity to detect significant differences in this group.…”
Section: Discussioncontrasting
confidence: 99%
“…Considering next the impact of genetic status on thalamic volumes, we found that C9orf72 expansion carriers exhibited more extensive thalamic atrophy, with more extreme negative w-scores relative to the sporadic groups. This was in line with another study looking at the extent of atrophy across the disease spectrum [43]. In our study, in particular, the pulvinar showed lower values in carriers compared to non-carriers in all clinical syndromes, confirming the specific involvement of this region in C9orf72-related neurodegenerative diseases [39,41,45].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Blood-oxygen-level-dependent (BOLD) signals measured by rs-fMRI are widely used for non-invasive mapping of brain function between neural activity and its accompanying hemodynamics. Recent studies have shown that the spreading of misfolded tau follows a disease-specific region-dependent pattern in the brain not only in the anatomically connected regions but also in the functionally connected regions in patients with AD ( Franzmeier et al, 2020 ; Vogel et al, 2021 ) and with FTD ( Kim et al, 2020 ; Spinelli et al, 2021 ; Young et al, 2021 ). The default mode network (DMN) is a set of network nodes consisting of the medial prefrontal cortex, the posterior cingulate/precuneus, inferior parietal lobe, lateral temporal cortex, and hippocampal formation ( Buckner and DiNicola, 2019 ).…”
Section: Functional Imagingmentioning
confidence: 99%